Neurobiology of learning and memory - Martinez, Joe L.; Kesner, Raymond P. (San Diego : Academic Press, 1998)
Neurobiology of Learning and Memory provides an excellent overview of current information on this fast-growing field of neurobiology. The contents have been structured for use as a course text or as a handy resource for researchers in neuro- and cognitive psychology. It discusses learning and memory from developmental, pharmacological, and psychobiological perspectives, as well as changes in learning and memory with age. Neurobiology of Learning and Memory also includes research on invertebrates and vertebrates, presenting basics in anatomy and development along with computational models. It is written in an easy-to-follow format with summaries at the end of each chapter. Key Features * Provides an overview of information on the neurobiology of learning and memory * Discusses learning and memory from developmental, pharmacological, and psychobiological perspectives, and changes in learning and memory with age * Includes research on invertebrates and vertebrates * Gives basics on anatomy and development * Written for easy comprehension with chapter summaries.
M.R. Rosenzweig, Historical Perspectives on the Development of the Biology of Learning and Memory. -- J.E. Black and W.T. Greenough, Developmental Approaches to the Memory Process. -- A.J. Silva and K.P. Giese, Gene Targeting: A Novel Window into the Biology of Learning and Memory. -- N.M. White and J.A. Salinas, Pharmacological Approaches to the Study of Learning and Memory. -- C. Sahley and T. Crow, Invertebrate Learning: Current Perspectives. -- J.L. Martinez, Jr., E.J. Barea-Rodriguez, and B.E. Derrick, Long-Term Potentiation, Long-Term Depression, and Learning. -- C.A. Barnes, Memory Changes during Normal Aging: Neurobiological Correlates. -- B.S. Kapp, A.J. Silvestri, and F.A. Guarraci, Vertebrate Models of Learning and Memory. -- F.B. Gershberg and A.P. Shimamura, The Neuropsychology of Human Learning and Memory. -- R.P. Kesner, Neurobiological Views of Memory. -- M.A. Gluck and C.E. Myers, Psychobiological Models of Hippocampal Function in Learning and Memory. -- Index.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Learning -- Psychological aspects; Memory -- Physiological aspects; Neurobiology; Electronic books